A Steady State Model for Burning Coal Mine Methane in a Reverse Flow Burner - Jinsheng Lv; Junrui Shi; Mingming Mao; Xiangjin Kong; Dan Zhou (Energies, 2021)
In this study, a steady state model for burning of coal mine methane in a Reverse Flow Burner (RFB) with full kinetics was developed by analogy of a steady counter-flow reactor, and the developed model was used for quick prediction of the lean combustibility limit (LCL). The model was successfully validated with experimental and numerical results, and it was shown that the developed model has excellent accuracy and computational efficiency. Good agreement between the predicted temperature, LCL, and the experiments was observed. The LCL of the equivalence ratio of 0.022 for methane/air mixture was obtained by the developed model. The model was then used to evaluate LCL for the RFB, focusing on the effect of heat loss and burner length on LCL. This indicated that the computational time using the developed model can be reduced by a factor of 1560 compared to the complete transient model.